Perceptions of Heat Risk Among Street Vendors, Its Associations With Knowledge and Impacts on Adaptive Measures in a Tropical Indian City - Kotharkar , Rajashree; Rajopadhye, Sagar (Geographica Pannonica, 2025)
There has been a concerning rise in heatwave-related deaths in India over the past few decades, particularly affecting the informal work sector exposed to high outdoor temperatures. This study aimed to understand how outdoor workers and street vendors in the landlocked tropical city of Nagpur perceive heat risks and how this perception relates to their knowledge and adaptive measures. A cross-sectional study using face-to-face surveys was conducted, introducing a novel Heat Risk Perception (HRP) Index to quantify participants’ risk perception. The findings revealed that 70% of street vendors had high HRP, with a mean index score of 0.72. Local knowledge and past heat experiences significantly influenced risk perception, despite gaps in scientific knowledge resulting from limited access to training programs. A strong positive relationship was observed between HRP and adjustments in work routines during hot weather, especially when vendors perceived health risks. This suggest that risk perception is crucial for adopting protective behaviours. Demographic factors did not significantly affect heat risk perception. Notably, 69% of vendors perceived themselves as vulnerable to heat’s negative effects, and perceived vulnerability emerged as a significant predictor of high HRP. The findings highlight the importance of risk perception in mitigating heat-related risks among vulnerable populations. The study’s results can inform the development of targeted interventions to protect street vendors and outdoor workers from heat-related risks.